Filling the Protein Gap in Ghana: The Role of Soy - Atuna, Richard Atinpoore; Amagloh, Flora Christine; Denwar, Nicholas Ninju; Asase, Vincent Richard; Faisal, Salifu; Baako, Emmanuel; Koomson, Gifty; Gulkirpik, Ece; Toc, Marco; Donnelly, Annette; Amagloh, Francis Kweku; Andrade Laborde, Juan E. (Frontiers in Sustainable Food Systems, 2022)
The study assessed the nutrient value and desirability of eight improved soybean varieties, for use in soymilk, tofu and as an ingredient to enhance staple foods. The soymilk, tofu, and soybean residue (okara) yields were determined across all varieties. The okara was subsequently used in composite with cassava, as a recipe refinement of gari, a popular cassava-based ready-to-eat food. Multiple composite ratios were compared against a control of 100% cassava gari; 80% cassava: 20% okara, 70% cassava: 30% okara, and 50% cassava: 50% okara. The soymilk and tofu from the various varieties and okara enriched-gari were also evaluated for proximate and sensory qualities (n = 50) using standard protocols. No differences (p > 0.05) existed among soybean varieties in terms of soymilk (p = 0.55; 13.0–14.1 L), tofu (p = 0.05; 0.12–0.15 kg/L) or okara (p = 0.08; 3.17–3.97 kg) yields. The proximate parameters evaluated for soymilk did not vary significantly (p > 0.05) among varieties. However, for total solids (3.33–7.93°Brix; p < 0.01) there were significant differences. Generally, there was an increasing trend in the crude protein, moisture, crude fat and total ash contents for the okara-enriched gari as the okara inclusion increased from 20 to 50%. Thus, the crude protein content of the 50% okara-enriched gari, the formulation with the highest okara incorporation was almost 11-times higher than the 100% cassava gari. The swelling capacity of the okara-enriched gari ranged from 3.29–5.47 and for water holding capacity 439.7–482.1%. The okara-enriched gari was equally preferred by consumers, except for colour which consumers were mostly indifferent towards. The 50%-okara enriched gari composite was compared equally with 100% cassava gari control. The sensory data showed that the “Favour” soybean variety was desirable for soymilk production while Salintuya 1 was desirable for tofu production. Recipe refinements using the desired varieties and compositing okara with cassava may help fill the protein gap among the vulnerable group in Ghana by improving the protein quality of ready-to-eat foods such as gari.